Effect of maleated linear low density polyethylene on the structure and mechanical properties of terpolymer acrylonitryle-butadiene-styrene based blend wastes - Jeziórska, R.; Szadkowska, A.; Abramowicz, A. (Polimery, 2012)
Modification of waste of acrylonitrile-butadiene-styrene terpolymer (ABS) or waste mixture containing 48.6 % of polyamide (PA), 27.2 % of polypropylene (PP), 10.6 % of ethylene-vinyl acetate copolymer (EVA) and 11.9 % of a natural filler was carried out by reactive extrusion in twin-screw corotating extruder. Comminuted wastes were mixed in selected ratios with linear low density polyethylene functionalized with maleic anhydride (MPE-LLD) used as a modifier. Thermogravimetric analysis as well as dynamic mechanical thermal analysis (DMTA) were used to study the re-granulated products obtained. Their mechanical and processing properties were evaluated. Scanning electron microscopy (SEM) was used to study the products structures. It has been found that an addition of the modifier used improved thermal properties and increased both elongation and impact strength of the blends based on ABS. All this proves the compatibilizing effect of a modifier. DMTA results also confirmed the compatibilizing effect of MPE-LLD due to the relaxation transitions ßPP, gPP and gPA disappearance.